2021
DOI: 10.1177/09544070211040349
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of turbulent flow and thermal behavior of automotive brake disc under repetitive braking

Abstract: The frictional brake system is the most safety critical equipment to decelerate or stop a vehicle. Thermal performance of the frictional region parts, disc and pads, necessitates to evaluate precisely in the design and test steps. In this study, a brake test setup was designed and fabricated with exactly the same braking components used in a common passenger vehicle as disc, pads, rim, tire, and dust shield to simulate the sequential braking. The local temperature on the disc and pads and the brake fluid press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The structure of the ventilated brake disc is constructed by constructing a series of radial vanes or pin-fins between two parallel friction surfaces, which not only increases the contact area with the air, but also allows the cold air around to be drawn into the channels of the disc to take away the heat, 81 so the optimization of the geometry of the ventilated brake disc is of great design significance to improve the heat dissipation capability of the brake. For example, Jafari and Akyüz 82 conducted a numerical study on the geometric parameters of radial vane disc brakes, and found that the ventilation gap has the greatest impact on the heat dissipation performance of the brake disc.…”
Section: Finite Element Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the ventilated brake disc is constructed by constructing a series of radial vanes or pin-fins between two parallel friction surfaces, which not only increases the contact area with the air, but also allows the cold air around to be drawn into the channels of the disc to take away the heat, 81 so the optimization of the geometry of the ventilated brake disc is of great design significance to improve the heat dissipation capability of the brake. For example, Jafari and Akyüz 82 conducted a numerical study on the geometric parameters of radial vane disc brakes, and found that the ventilation gap has the greatest impact on the heat dissipation performance of the brake disc.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…The current research methods mainly include brake interface temperature test, 25 analytical calculation, 2631 and numerical analysis. 3292 Among them, the experimental exploration method is effective but costly, the analytical calculation of temperature field is accurate but difficult to solve, and the numerical analysis uses numerical methods to find the approximate solution, which is not very accurate, but with the continuous development of computers, the...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, 10 many methods have been used to study the flow field and heat transfer characteristics in the brake disc passage.…”
Section: Introductionmentioning
confidence: 99%